2024
DOI: 10.1021/acsami.3c18862
|View full text |Cite
|
Sign up to set email alerts
|

Non-Electroconductive Polymer Coating on Graphite Mitigating Electrochemical Degradation of PTFE for a Dry-Processed Lithium-Ion Battery Anode

Taegeun Lee,
Jiwoo An,
Woo Jun Chung
et al.

Abstract: Polytetrafluoroethylene (PTFE)-based dry process for lithium-ion batteries is gaining attention as a battery manufacturing scheme can be simplified with drastically reducing environmental damage. However, the electrochemical instability of PTFE in a reducing environment has hampered the realization of the high-performance dry-processed anode. In this study, we present a non-electroconductive and highly ionic-conductive polymer coating on graphite to mitigate the electrochemical degradation of the PTFE binder a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…The high plasticity of PTFE allows forming fibers under shearing to connect electrode particles. However, there are challenges associated with PTFE in LIB anodes since it is known for its unstability at low potential, 16 contributing to capacity loss in the early stages of battery cycling. 14,17 PTFE production has also been singled out as having significant environmental impacts.…”
mentioning
confidence: 99%
“…The high plasticity of PTFE allows forming fibers under shearing to connect electrode particles. However, there are challenges associated with PTFE in LIB anodes since it is known for its unstability at low potential, 16 contributing to capacity loss in the early stages of battery cycling. 14,17 PTFE production has also been singled out as having significant environmental impacts.…”
mentioning
confidence: 99%
“…A full cell assembled with a commercial NCM electrode as the cathode was tested, and the results showed that the PEO and P(VDF-TrFE-CFE) layers increased the initial discharge capacity of the battery from 157.7 mAh/g (uncoated graphite anode) to 185.1 mAh/g and 182.5 mAh/g, respectively, and the ICE was improved from 67.2% (uncoated graphite anode) to 79.1% and 77.8%; this work provides a reliable idea for solving the instability problem of PTFE in anode. To solve this problem, a strategy was proposed and experimentally verified by Taegeun Lee et al [83] in 2024, in which the graphite particles were coated with a layer of PEO or poly(vinylidene-fluoride−trifluoroethylene−chlorofluoroethylene) (P(VDF-TrFE-CFE)) that does not conduct electrons but conducts ions to partially block the occurrence of side reactions of PTFE at the anode (Figure 17). A full cell assembled with a commercial NCM electrode as the cathode was tested, and the results showed that the PEO and P(VDF-TrFE-CFE) layers increased the initial discharge capacity of the battery from 157.7 mAh/g (uncoated graphite anode) to 185.1 mAh/g and 182.5 mAh/g, respectively, and the ICE was improved from 67.2% (uncoated graphite anode) to 79.1% and 77.8%; this work provides a reliable idea for solving the instability problem of PTFE in anode.…”
Section: The Application Of Ptfe In Anodesmentioning
confidence: 99%
“…In the same year, Ziqi Wei et al [84] prepared a dry graphite anode using PEO-coated graphite with PTFE as the fibrillated binder, and compared the contents of the side reaction components between the uncoated graphite anode and PEO-coated graphite anode with an XPS test, which proved that the PEO-coated graphite anode had fewer side reactions; when the half-cell was assembled using a lithium foil as the counter electrode for the test, the PEO-coated graphite anode showed a much higher CE of 90.9% than that of the uncoated graphite anode (69.5%), which again verified the feasibility of this strategy (Figure 18). To solve this problem, a strategy was proposed and experimentally verified by Tae geun Lee et al [83] in 2024, in which the graphite particles were coated with a layer o PEO or poly(vinylidene-fluoride−trifluoroethylene−chlorofluoroethylene) (P(VDF-TrFE CFE)) that does not conduct electrons but conducts ions to partially block the occurrenc of side reactions of PTFE at the anode (Figure 17). A full cell assembled with a commercia NCM electrode as the cathode was tested, and the results showed that the PEO and P(VDF-TrFE-CFE) layers increased the initial discharge capacity of the battery from 157. mAh/g (uncoated graphite anode) to 185.1 mAh/g and 182.5 mAh/g, respectively, and th ICE was improved from 67.2% (uncoated graphite anode) to 79.1% and 77.8%; this work provides a reliable idea for solving the instability problem of PTFE in anode.…”
Section: The Application Of Ptfe In Anodesmentioning
confidence: 99%